Pilihan Masyarakat dalam Pengadaan Karnaval di Desa Mumbulsari - Fatkurohman Nur Rangga; Irfan Khairan Ali; Triyana Oktavia (Jurnal Kajian dan Penelitian Umum, 2023)
The enthusiasm of the local community towards the implementation of local cultural activities has always been eagerly anticipated. In this regard, the community of Desa Mumbulsari, Jember Regency, actively contributes and willingly expends significant effort and a substantial amount of money to organize a carnival event commemorating the Independence Day of Indonesia. The purpose of this article is to showcase the active participation of the Desa Mumbulsari community in the execution of the carnival. Within this article, the community's choice regarding the risks associated with organizing the carnival becomes the focal point of analysis. The research methodology employed is qualitative, utilizing a phenomenological approach involving observation and interview methods.